Evaluation of predictive factors for conversion of laparoscopic cholecystectomy - Gabriel, R; Kumar, S; Shrestha, A (Kathmandu University Medical Journal, 2009)
Background: Laparoscopic cholecystectomy has now replaced open cholecystectomy for the treatment of gallbladder diseases. However, certain cases still require conversion to open procedures. This study identifies and evaluates risk factors that may predict conversion from laparoscopic to an open procedure. Objectives: To identify and evaluate the predictive factors for conversion of laparoscopic to open cholecystectomy. Materials and methods: A total of 234 Laparoscopic cholecystectomies were attempted at the Kasturba Medical College Hospital, Manipal, from January 2003 to July 2005. Of these, 61 had to be converted to open cholecystectomy. A retro and prospective analysis of different parameters, including Patient factors, Intra-operative factors and Surgeon factors were performed. Results: Sixty one (26.1%) laparoscopic cholecystectomies required conversion. Factors contributing to conversion included male sex, age group of 31-40 years, over weight and history of biliary pain within last two to four months, ultrasonography findings of multiple calculi and gall bladder wall thickness of more than 3 mm. Intraoperative gall bladder perforation with spillage of its contents in abdominal cavity and dense adhesions with difficult anatomy resulted in higher conversion rates. Surgery performed by surgeons in learning phase of laparoscopic surgery was more prone to conversion. Conclusion: Patient factors, presentation, preoperative ultrasonography findings and surgeon's experience, all contribute to the possibility of conversion of laparoscopic cholecystectomy. Knowledge of these factors may help in preinformation to patient for psychological preparations for conversion and an experienced surgeon can plan to operate on these patients. Key words: Cholecystectomy, laparoscopy, conversion. doi: 10.3126/kumj.v7i1.1761       Kathmandu University Medical Journal (2009), Vol. 7, No. 1, Issue 25, 26-30